CRISPR‐Cas9 Genome Editing and Rapid Selection of Cell Pools. Issue 12 (22nd December 2022) - Stoyko, Daniel; O, Timothy; Hernandez, Adrianna; Konstantinidou, Parthena; Meng, Qingcai; Haase, Astrid D.
Abstract: The harnessing of the CRISPR‐Cas9 system allows for quick and inexpensive genome editing in tissue culture models. Traditional CRISPR‐Cas9 genome editing techniques rely on the ability of single progenitor cells to expand into new pools in a process known as clonal expansion. This is a significant technical challenge that is difficult to overcome for nontransformed cell culture models such as Drosophila ovarian somatic sheath cells (OSCs). OSCs are a unique ex vivo model for epigenetic regulation by PIWI‐interacting RNAs (piRNAs) that establish restriction of mobile genetic elements in germ cells to protect genome integrity. Here, we provide a protocol to generate endogenously tagged proteins and gene knockouts without the need for clonal selection. We combine CRISPR‐Cas genome editing and knockin of antibiotic selection markers to generate edited cell pools. At the example of Drosophila piwi in OSCs, we demonstrate a strategy that relies on the insertion of an artificial intron to accommodate a selection marker with minimal disturbance of the resulting mRNA. In brief, our donor cassette contains a peptide tag and an optimized intron that accommodates a selection marker driven by an independent promoter on the other genomic strand. The selection marker is transcribed as an independent mRNA, and the intron is efficiently removed from the mRNA encoding the endogenously tagged (endo‐tagged) piwi gene. The endo‐tagged Piwi protein is expressed at wild‐type levels and appropriately localizes to the nucleus of OSCs. We also describe strategies for C‐terminal tagging and generation of knockout alleles in OSCs and in human embryonic kidney cells, discuss different design strategies, and provide a plasmid toolkit (available at Addgene). Our protocol enables robust genome editing in OSCs for the first time and provides a simple and time‐saving alternative for other cell culture systems. Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1 : Design and cloning of single‐guide RNA plasmids Basic Protocol 2 : Design and cloning of donor template plasmids for epitope tagging Alternate Protocol : Design and cloning of donor template plasmids for gene knockout Basic Protocol 3 : Transfection and selection of edited cell pools